2023
DOI: 10.31275/20232967
|View full text |Cite
|
Sign up to set email alerts
|

Assessing 36 Years of the Forced Choice Design in Extra Sensory Perception Research: A Meta-Analysis, 1987 to 2022

Lance Storm,
Patrizio Tressoldi

Abstract: This meta-analysis is an update of Storm, Tressoldi, and Di Risio (2012); a meta-analysis on forced-choice ESP studies (1987 to 2010), which use targets such as card symbols, pictures, and letters. We formed two datasets: New Studies #1 (studies that included actual hit rates) and New Studies #2 (Reaction Time [‘RT’] Studies; which are studies that measured only reaction time, not hits, as indicators of psi responses). New Studies #1: For the period 2011 to 2022, a homogeneous dataset of 38 studies yielded a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Th is was the approach adopted e.g., by McDonough et al (1992) and Moulton & Kosslyn (2008) -see also Acunzo et al (2013) for a critical review -and corresponding to Figure 2, side c. For this approach to be truly informative, individual 'hit' trials must be observed and identifi able as veridical ESP hits. With very small eff ect sizes such as the ones reported for forced-choice designs (~0.02; Storm & Tressoldi, 2023), most hits will be imputable to chance, according to the expected 'hit' probability under the null hypothesis. In that case, the signal-to-noise ratio for the diff erence in brain activity between 'hit' and 'miss' trials will be extremely low, and any existing ESP signal will be extremely diffi cult to observe.…”
Section: Neuroimaging and Esp: Approaches And Frameworkmentioning
confidence: 93%
See 2 more Smart Citations
“…Th is was the approach adopted e.g., by McDonough et al (1992) and Moulton & Kosslyn (2008) -see also Acunzo et al (2013) for a critical review -and corresponding to Figure 2, side c. For this approach to be truly informative, individual 'hit' trials must be observed and identifi able as veridical ESP hits. With very small eff ect sizes such as the ones reported for forced-choice designs (~0.02; Storm & Tressoldi, 2023), most hits will be imputable to chance, according to the expected 'hit' probability under the null hypothesis. In that case, the signal-to-noise ratio for the diff erence in brain activity between 'hit' and 'miss' trials will be extremely low, and any existing ESP signal will be extremely diffi cult to observe.…”
Section: Neuroimaging and Esp: Approaches And Frameworkmentioning
confidence: 93%
“…Characterizing these psi-associated states may, therefore, be a key element to the understanding of ESP (Fig. 2, side a) and is an approach highly compatible with free-response designs, which appear to be the way forward for this fi eld, given the higher eff ect sizes (Storm & Tressoldi, 2023;Tressoldi & Katz, 2023). Various tools and approaches have been developed to probe the subjective experience of individuals undergoing these ASCs, but come with methodological challenges: concurrent experience sampling may interfere with the experience itself, while retrospective interviews can suff er from various biases, distortions, and poor recollection and temporal precision (see Cardeña & Pekala, 2014 for a thorough discussion).…”
Section: Neuroimaging and Esp: Approaches And Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…-Assessing 36 Years of the Forced Choice Design in Extra Sensory Perception Research: A Meta-Analysis, 1987 to 2022 (Storm & Tressoldi, 2023).…”
Section: Included Meta-analysesmentioning
confidence: 99%
“…Most studies that have used Zener cards employ a forced-choice design, a method where participants guess or select from limited, known options without sensory information about the targets (Storm, & Tressoldi, 2023). In relation to this, no significant improvements in the effectiveness of this design were observed from 1987 to 2022, with calculated effect sizes from naive participants being trivially small (0.01), suggesting minimal practical relevance (Storm, & Tressoldi, 2023). Specifically, in contexts involving participants from the general population (who are not presumed to be particularly "gifted"), statistically significant effects have rarely been achieved.…”
Section: Zener Cardsmentioning
confidence: 99%